A Case of Acute Autoimmune Hepatitis Superimposed on Chronic Hepatitis B Infection. (1st April 2018) - Sostre, Vanessa; Patel, Hiren G.; Mohamed, Abdalla; Volfson, Ariy
Abstract : Autoimmune hepatitis has been associated with chronic HCV infection, but there are only few cases reported of HBV infection as a possible trigger. We present a case of a young male who was diagnosed with acute autoimmune hepatitis superimposed on existent chronic HBV infection. A 30-year-old Hispanic male with no past medical history presented to the hospital with complaints of few days of generalized weakness. Laboratory findings were significant for elevated liver enzymes: AST, 1164 U/L; ALT, 1461 U/L; total bilirubin, 2 MG/DL; and alkaline phosphatase, 75 IU/L. Extensive workup was done to find the etiology for elevated liver enzymes. Only blood work that came back positive was for chronic HBV infection and elevated immunoglobulin G (IgG) level 1937 mg/dL. HBV viral load was 42, 900, 000 IU/mL. The patient was started on tenofovir 300 mg daily. Liver biopsy was done which was consistent with autoimmune hepatitis. Prednisone 60 mg daily was started. Six months later, blood work showed completely normal liver enzymes and total IgG. Hepatotropic viruses have been proposed as triggering factors for several autoimmune diseases. There are theories suggesting that similarity in viral epitope and self-proteins expression on liver cells' surface causes a cross-reactive immunologic response and possible viral-induced autoimmune hepatitis.